Analisis Manejemen Resiko Keamanan Data Sistem Informasi Berdasarkan Indeks Keamanan Informasi (KAMI) ISO 27001:2013 - Silvia Paramita; Sandy Akbar Siregar; Rissa Azzahra Damanik; Muhammad Dedi Irawan (Bulletin of Information Technology (BIT), 2022)
In this era of globalization, technological advances, especially in the field of information systems, are very rapid. Especially in schools which are one of the fields of education that require the involvement of information technology in data management and security. Similar to management reports on the number of students present, absent and sick. Likewise with book managers, librarians count or verify the number of subject books, story books, and other types of literature. By implementing a system that can facilitate operations in schools using software, it is very important for schools to build a reliable information system to control the smooth movement of data and help and speed up data processing in schools. SENIOR HIGH SCHOOL. NEGERI 6 MEDAN which has the address, was chosen as the location for observing the activities in this activity